Extraction of B-carotene from natural substrates using supercritical ethane and ethylene - Talisic, Geraldo C.
Extraction of biomolecules like high-value vitamins has been the focused of supercritical fluid separation and the use of carbon dioxide as the supercritical solvent has been employed rather extensively. The use of supercritical fluid as a solvent of choice was driven by both environmental and health concerns. The solubility of a substance in the supercritical fluid is a measure of how many moles of solute will be dissolved in one mole of supercritical fluid at a given temperature and pressure. As such, solubility data will therefore define the technical feasibility of potential extraction process and can be used to establish solvent-to-feed ratios. The use of ethane and ethylene as alternative supercritical solvents to carbon dioxide is proven to be more effective in the separation of high molecular weight materials of biological origin. The solubility of β-carotene in SC ethane and ethylene is twice or thrice as much as in carbon dioxide at a specific at a specified reduced temperature and reduced density. The measured solubilities in carbon dioxide, ethane and ethylene were correlated using both density-based correlation and equation of state making use of the equation first developed by Chrastil and the Peng-Robinson Equation of State, respectively. The extraction of β-carotene from natural substrates like algae, carrot and tomato using supercritical ethane and ethylene was attempted to determine the viability and efficiency. The supercritical fluid extraction provides better alternative in terms of selectivity than solvent extraction which was validated by the results in the tomatoextract. In terms of yield, algae produced the highest yield of β-carotene compared to tomato and carrot at a given density. The results might either mean that more β-carotene ,olecules are easily and readily avai;able to SCF solvent in the algal matrix or the low yields on tomato and carrot were a result of the low concentration of β-carotene on those substances. However, tomato and carrot extract yield purer extracts than algae do as can be seen in their respective chromatograms.